2016
DOI: 10.4162/nrp.2016.10.4.448
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional aspects of night eating and its association with weight status among Korean adolescents

Abstract: BACKGROUND/OBJECTIVESA growing body of research has indicated that night eating could be associated with poor diet quality and negative health outcomes. This study examined the nutritional aspects of night eating, its related factors, and the association between night eating and body weight among Korean adolescents.SUBJECTS/METHODSThis study analysed the data from a one day 24-hour dietary recall as well as a demographic survey of 1,738 Korean adolescents aged 12 to 18-years-old obtained from the 2010-2012 Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
(63 reference statements)
3
30
1
Order By: Relevance
“…Although studies are too limited to make firm conclusions regarding nutritional characteristics related to night eating, the available information points towards maternal night eating being generally associated with less healthy dietary intake, low diet quality and reductions in circulating levels of certain micronutrients during pregnancy. This is supported by studies in teenagers and adults, which have consistently reported that individuals with a delayed temporal distribution of food intake (i.e., night-eaters, late-eaters, an evening chronotype, night-shift workers) were mostly engaged in unhealthy eating behavior with poor diet quality [59,60,65]. Overall, it seems that diet composition among night eaters is an important aspect to consider when studying night eating and health implications.…”
Section: Nutritional Aspects Of Night Eatingmentioning
confidence: 82%
“…Although studies are too limited to make firm conclusions regarding nutritional characteristics related to night eating, the available information points towards maternal night eating being generally associated with less healthy dietary intake, low diet quality and reductions in circulating levels of certain micronutrients during pregnancy. This is supported by studies in teenagers and adults, which have consistently reported that individuals with a delayed temporal distribution of food intake (i.e., night-eaters, late-eaters, an evening chronotype, night-shift workers) were mostly engaged in unhealthy eating behavior with poor diet quality [59,60,65]. Overall, it seems that diet composition among night eaters is an important aspect to consider when studying night eating and health implications.…”
Section: Nutritional Aspects Of Night Eatingmentioning
confidence: 82%
“…Among four lifestyle behaviours we examined, dinner timing and outside playtime were not consistently associated with children's overweight. Dinner timing is a behaviour that affects skipping breakfast 38 and skipping breakfast is associated with children's overweight. 39 Thus, dinner timing is considered as an important dietary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of eating out, individuals who ate out at least once daily were compared with others who ate out less frequently. These definitions have been used in previous studies which compared adolescents based on breakfast skipping [ 17 ], night eating [ 18 ], and eating out [ 19 ].…”
Section: Methodsmentioning
confidence: 99%